2021
DOI: 10.3390/plants10050970
|View full text |Cite
|
Sign up to set email alerts
|

Towards Biological Control of Aspergillus carbonarius and Botrytis cinerea in Grapevine Berries and Transcriptomic Changes of Genes Encoding Pathogenesis-Related (PR) Proteins

Abstract: Grapevine bunch rot, caused by Botrytis cinerea and Aspergillus carbonarius, causes important economic losses every year in grape production. In the present study, we examined the plant protective activity of the biological control agents, Paenibacillus alvei K165, Blastobotrys sp. FP12 and Arthrobacter sp. FP15 against B. cinerea and A. carbonarius on grapes. The in vitro experiments showed that strain K165 significantly reduced the growth of both fungi, while FP15 restricted the growth of A. carbonarius and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Recently, it has been demonstrated by transcriptomic analysis of the genes encoding the pathogenesis-related proteins showed that genes PR 2 and PR 3 was found to be upregulated by Paenibacillus alvei K165 and Blastobotrys sp. FP12 inoculation in grape berries, which encode the β-1,3-glucanase and chitinase, respectively, which indicates the activation of the defense response against grapevine bunch rot caused by Botrytis cinerea [ 117 ]. Yadav et al [ 102 ] reported that two pathogenesis-related genes ( PR-2 and PR-5 ) were significantly expressed in chilli bioprimed seeds under Colletotrichum truncatum -challenged conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated by transcriptomic analysis of the genes encoding the pathogenesis-related proteins showed that genes PR 2 and PR 3 was found to be upregulated by Paenibacillus alvei K165 and Blastobotrys sp. FP12 inoculation in grape berries, which encode the β-1,3-glucanase and chitinase, respectively, which indicates the activation of the defense response against grapevine bunch rot caused by Botrytis cinerea [ 117 ]. Yadav et al [ 102 ] reported that two pathogenesis-related genes ( PR-2 and PR-5 ) were significantly expressed in chilli bioprimed seeds under Colletotrichum truncatum -challenged conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates of this genus are, therefore, of interest for study as potential BCAs; in fact, Arthrobacter sp. strains such as FP15 have been found to secrete compounds that efficiently inhibit A. carbonarius growth [29]. Other species are known to secrete chitinase and antibiotic compounds with inhibitory effects on a wide range of plant pathogenic or xylophagous fungi [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…This includes the stimulation of defense-related genes in plants, such as pathogen resistance genes (PR proteins), as well as the expression of genes encoding specific metabolites or proteins that are involved in the defense setup of the plant system ( Figure 3 ) [ 140 ]. For example, the activation of multiple defense responses in the biocontrol activity of several examined BCAs to combat grapevine bunch rot caused by B. cinerea and Aspergillus carbonarius is indicated by transcriptomic analysis of genes encoding pathogenesis-related proteins PR2, PR3, PR4, and PR5 [ 141 ]. Beneficial microbes cause early plant ISR events such as increased expression of pathogenesis-related PR genes, increased activity of defense-related substances such as phenylalanine ammonia-lyase, polyphenol oxidase, peroxidase, β-1,3, glucanase, chitinase, and the accumulation of reactive oxygen species [ 142 , 143 ].…”
Section: Bcas Modes Of Actionmentioning
confidence: 99%